Beyond the Cessation Clause: Rwandan Refugees in Uganda—From Refugees to East African Citizens? - Ahimbisibwe, Frank (ASC-TUFS Working Papers, 2, 103-127., 2022)
Since 2002, Uganda has been trying to find a durable solution to the Rwandan refugee issue without success. Despite various attempts at (in)voluntary repatriation, the majority refuse to return. Resettlement is not possible, and local integration is yet to be explored. Simultaneously, the recommendation for the cessation of refugee status by the United Nations High Commissioner for Refugees has not addressed the problem. We analysed the prospects and challenges of granting East African citizenship to Rwandan refugees by issuing East African Community (EAC) passports or residence permits that would give them freedom of mobility, residence, and employment in the EAC in accordance with the Common Market Protocol. Searching for a durable solution at the EAC level comes at a time when efforts to establish the East African federation continue. This has the potential to end one of the most protracted refugee situations, promoting the rights of Rwandan refugees, and enhancing people-centred regional integration
Keywords: Rwandan refugees; Cessation clause; Durable solutions; East African community; Mobility; Citizens; Uganda; Rwanda